DECENTRALIZATION AND EQUITY: A REVIEW OF THE LATIN AMERICA LITERATURE (2006)
A literature review of published articles were done to set a description of the historical background of health reforms in Latin America and to provide a brief description of the process of decentralization in countries such as Colombia, Brazil, Chile, Mexico and Costa Rica in order to illustrate different tendencies in the transformations of the health systems in the region. This literature review demonstrated the increasing need of more systematic studies in this area. Although decentralization in theory may be a powerful mechanism to promote equity in health, it may be insufficient or prejudicial in the context of unclear policy intended to promote equity by the state. Moreover, the role of other concomitant phenomena like privatization and shortage of state funding of health must also be discussed. However, the evidence regarding the results of decentralization in LAC is still contradictory and ambiguous. It is not clear that its achievements could reach its intentions of improved equity in health in the region.